2010
DOI: 10.1007/s12291-010-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in pathogenesis of nephrotic syndrome

Abstract: Nephrotic syndrome is the common chronic disorder characterized by alteration of permeability of the glomerular capillary wall, resulting in its inability to restrict the urinary loss of proteins. Nephrotic syndrome is characterized by heavy proteinuria, hypoalbuminemia, hyperlipidemia associated with peripheral edema. The molecular basis of glomerular permselectivity remains largely unknown. In recent years it has been proposed that Nephrotic syndrome is a consequence of an imbalance between oxidant and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The change in leukocyte activation and migration may influence the course of NS, with the possible participation of these cells in renal oxidative stress and albuminuria induction in the early stage of the disease. Human patients with NS exhibit increased ROS production in the plasma associated with a reduction in the amount of plasma albumin [ 9 ]. In an animal model of doxorubicin-induced NS, increased TBARS production has been found [ 8 ], associated with a reduction in the activity of catalase in renal tissue [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in leukocyte activation and migration may influence the course of NS, with the possible participation of these cells in renal oxidative stress and albuminuria induction in the early stage of the disease. Human patients with NS exhibit increased ROS production in the plasma associated with a reduction in the amount of plasma albumin [ 9 ]. In an animal model of doxorubicin-induced NS, increased TBARS production has been found [ 8 ], associated with a reduction in the activity of catalase in renal tissue [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney injury in INS may also be related to oxidative tissue damage through the increased production of reactive oxygen species (ROS) [ 8 10 ]. Recent studies have shown that patients with NS patients have higher levels of ROS than healthy controls [ 9 ]. Lipid peroxidation products have been associated with animal models of NS [ 8 , 10 , 11 ], while changes in the activity of superoxide dismutase (SOD) and catalase have been detected in the plasma of patients [ 9 ] and the renal tissue of animals with NS [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it appears that SOD activity is not altered consistently in nephrotic syndrome. Also, whereas Ghodake et al [29] found unchanged ascorbic acid concentrations, other studies noted reduced levels in active disease compatible with consumption as part of antioxidant defense mechanisms [3,30]. Dwivedi and Sarkar [30] reported decreased levels of zinc during the active phase of nephrotic syndrome, with a significant increase following antioxidant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Malonyldialdehyde (MDA), by-product of lipid peroxidation, is often tested to predict the status of ROS indirectly. 7,8 Also, the micronutrients including vitamin C and E are non-enzymatic antioxidants that will decline due to the consumption of oxidative stress. In this sense, it is reasonable to hypothesize that the alterations of MDA, vitamin C and E may be associated with INS.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies [9][10][11][12][13][14][15][16] have showed the alterations of these parameters in the INS subjects. However, the relative small number of participants limited the statistical power, and some of the results were in conflict.…”
Section: Introductionmentioning
confidence: 99%